2019
DOI: 10.1080/02670836.2019.1625555
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low magnitude plastic strains on residual stress in 7075 aluminium alloy

Abstract: The effect of post quench delay on residual stress has been determined by subjecting four rectilinear blocks of quenched 7075, containing large residual stress magnitudes, to small (<1.0%) plastic strains applied by cold compression. One experiment kept the plastic strain the same in all samples (∼0.12%) by cold compressing simultaneously in one pressing. The second pressed the blocks separately to the same strain (∼0.45%). The post quench delays were <10, 60, 120 and 240 min. The residual stresses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…7075-T651 Al alloy is extensively used in the components (cabin frame, plane's wings, the skin of wings, and bearing beam) of automotive and aerospace components, which gives rise on superior performances such as the low density, high specific strength, strong corrosion-resistance, good fracture toughness [1][2][3]. However, the component has different degrees of deformation due to the stress distribution and materials surface hardness change after shot peening (SP), which may lead to surface stress reorganization [4] and affect the performance [5,6]. How to accurately control the surface characteristics of materials such as stress and hardness by shot peening has become a research hotspot [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…7075-T651 Al alloy is extensively used in the components (cabin frame, plane's wings, the skin of wings, and bearing beam) of automotive and aerospace components, which gives rise on superior performances such as the low density, high specific strength, strong corrosion-resistance, good fracture toughness [1][2][3]. However, the component has different degrees of deformation due to the stress distribution and materials surface hardness change after shot peening (SP), which may lead to surface stress reorganization [4] and affect the performance [5,6]. How to accurately control the surface characteristics of materials such as stress and hardness by shot peening has become a research hotspot [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[ 159 ] Moreover, it was revealed that surface compressive residual stress is influenced by the implementation of cold compression to a higher degree than the interior tensile stresses. [ 160 ] Accomplishing slitting technique coupled with statistical analyses, Asghari et al [ 161 ] scrutinized the impact of the cooling condition on the residual stresses of CFRP shells, reporting that temperature differences between curing and cooling conditions induce thermal shock, resulting in the building up of high residual stress levels, which, in turn, accelerates the structural failure. Simultaneous cooling conditions and CNT reinforcement effects were studied in another paper, [ 162 ] indicating that the influence of cooling conditions on the residual thermal stresses becomes more significant when the CNT percentage decreases.…”
Section: Origins and Effectsmentioning
confidence: 99%